ADAPTIVE DIFFERENTIAL TRANSFORMATIONS AND THEIR APPLICATION FOR SOLVING BOUNDARY-VALUE PROBLEMS - Baranov , V. L. (Problems of Informatization and Control, 2021)
Differential transformations are proposed, which are adapted to the solution area of the boundary set of mathematical phics. An example of the use of adaptive differential transformations for solving a boundary value problem is given.